WEB-BASED RESTAURANT FOOD ORDERING APPLICATION INFORMATION SYSTEM USING AQILE DEVELOPMENT METHOD - Anderias Kedu Lere; Gergorius Kopong Pati; Emerensiana Dappa Ege (CV. Fahr Publishing, 2023)
The information system regarding restaurant food is still little known to the public, especially those who often use internet access and who want to order catering online. The ordering information system is still manual so to get the information people have to come directly. The aim of this research is to analyze and develop a web-based restaurant food ordering system using the Agile Development method that is efficient and makes the ordering process easier for customers and restaurants. This research will use agile methods to develop a web-based restaurant food ordering system that makes it easier for customers to order food and helps restaurants manage food orders efficiently.